Synthesis of silver nanoparticles using a modified Tollens’ method in conjunction with phytochemicals and assessment of their antimicrobial activity - AbuDalo, Muna A.; Al-Mheidat, Ismaeel R.; Al-Shurafat, Alham W.; Grinham, Colleen; Oyanedel-Craver, Vinka (PeerJ, 2019)
Background Silver nanoparticles (AgNPs) have attracted great attention due to their outstanding electrical, optical, magnetic, catalytic, and antimicrobial properties. However, there is a need for alternative production methods that use less toxic precursors and reduce their undesirable by-products. Phyto-extracts from the leaves of olive and rosemary plants can be used as reducing agents and (in conjunction with Tollens’ reagent) can even enhance AgNP antimicrobial activity. Methods Conditions for the proposed hybrid synthesis method were optimized for olive leaf extracts (OLEs) and rosemary leaf extracts (RLEs). The resultant AgNPs were characterized using UV–visible spectroscopy, an environmental scanning electron microscope, and Dynamic Light Scattering analysis. An atomic absorption spectrophotometer was used to measure AgNP concentration. Fourier transform infrared spectroscopy (FTIR) was used to determine the specific functional groups responsible for the reduction of both silver nitrate and capping agents in the leaf extract. Additionally, the antimicrobial properties of the synthesized AgNPs were assessed against Gram-negative bacteria (Escherichia coli and Salmonella enterica) and Gram-positive bacteria (Staphylococcus aureus), by using both the Kirby–Bauer and broth microdilution methods on Mueller–Hinton (MH) agar plates. Results and Discussion A simple, feasible, and rapid method has been successfully developed for silver nanoparticle synthesis by reducing Tollens’ reagent using leaf extracts from olive and rosemary plants (widely available in Jordan). Scanning electron microscopy images showed that the method produces AgNPs with a spherical shape and average core sizes of 45 ± 2 and 38 ± 3 nm for OLE and RLE, respectively. A negative zeta potential (ζ) of −43.15 ± 3.65 mV for OLE-AgNPs and −33.65 ± 2.88mV for RLE-AgNPs proved the stability of silver nanoparticles. FTIR spectra for AgNPs and leaf extracts indicated that the compounds present in the leaf extracts play an important role in the coating/capping of synthesized nanoparticles. The manufactured AgNPs exhibited an antibacterial effect against Escherichia coli and Staphylococcus aureus with minimum inhibitory concentrations (MIC) of 9.38 and 4.69 μl/ml for OLE-AgNPs and RLE-AgNPs, respectively. The MIC for Salmonella enterica were 18.75 μl/ml for both OLE-AgNPs and RLE-AgNPs. Furthermore, our results indicated that the RLE-AgNPs exhibited a stronger antibacterial effect than OLE-AgNPs against different bacteria species. These results contribute to the body of knowledge on nanoparticle production using plant-mediated synthesis and performance. They also offer insights into the potential for scaling up this production process for commercial implementation.
Keywords: Silver nanoparticles (AgNPs); Tollens’ method; Olive leaves extract (OLE); Rosemary leaves extract (RLE); Antimicrobial effect